O muzyce w czasach pandemii COVID-19: socjologiczna interpretacja zmiany praktyk muzycznych na poziomie wykonawczym i odbiorczym - Jabłońska, Barbara (Załącznik Kulturoznawczy, 2022)
The article aims to present the issues of musical practices in the times of the COVID-19 pandemic. The SARS-CoV-2 virus has completely disrupted the lives of people around the world, also hitting the world of music with force. The main axis of consideration is the belief in the social and communicative nature of music and the essence of musical practices in the collective dimension of human existence. The pandemic reality turned out to be a specific testing ground for these practices – which contributed significantly to the modification of human activities. The theoretical underpinning of the considerations is Stanisław Ossowski’s reflections on the communicative value of a musical work and elements of Alfred Schütz’s theory regarding the interactive dimension of musical practices. The article discusses such important aspects of people’s musical practices in pandemic times as their digitization and networking, social norms and rituals, artist-artist and artist-audience relations in the virtual world, domestication of musical practices, or epidemic rules. The whole discussion is guided by the assumption of the extraordinary social power of music, referring to the reflection on music and society as perceived by Karol Szymanowski and Arthur Schopenhauer. The conclusion of the article leads to the belief that the world of music will not be the same as before the pandemic, and hybrid solutions for combining virtual music practices with traditional ones (face-to-face) will certainly contribute to dynamic changes in the musical culture of societies around the world.